2013
DOI: 10.1080/01694243.2012.697371
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of PLGA nanofibrous biocomposites using flavonoids for biomedical applications

Abstract: Rutin-containing poly(L-lactide-co-glycolide) (PLGA) nanofibrous biocomposites were prepared by electrospinning technique and antibacterial properties of the biocomposites were examined. Two types of bacterial strains, Staphylococcus aureus and Klebsiella pneumoniae were used in this test. The results showed that the rutin-containing PLGA nanofibrous biocomposites exhibited significant antibacterial effects against both the bacteria. Human nasopharyngeal epidermoid carcinoma (KB) epithelial cells were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It is noted that the electrospun pullulan/PVA/rutin nanofibrous mats had greater tensile stress than that of pullulan/PVA, and the ultimate tensile strength exhibited an increasing trend as the content of rutin increased, which indicated that the addition of rutin was capable of enhancing the mechanical properties of the nanofibrous mats. Rutin has stiff aromatic rings and ethylene dioxy rings in its structure [ 26 ]; meanwhile, rutin was capable of randomly dispersing in the electrospun nanofibers [ 22 ]. Thus, the addition of a limited amount of rutin can enhance the strength to some extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that the electrospun pullulan/PVA/rutin nanofibrous mats had greater tensile stress than that of pullulan/PVA, and the ultimate tensile strength exhibited an increasing trend as the content of rutin increased, which indicated that the addition of rutin was capable of enhancing the mechanical properties of the nanofibrous mats. Rutin has stiff aromatic rings and ethylene dioxy rings in its structure [ 26 ]; meanwhile, rutin was capable of randomly dispersing in the electrospun nanofibers [ 22 ]. Thus, the addition of a limited amount of rutin can enhance the strength to some extent.…”
Section: Resultsmentioning
confidence: 99%
“…Rutin was found to be photo-stable and capable of enhancing the defense system against environment stresses, including low temperature, UV light, and desiccation [ 20 , 21 ]. Xing et al [ 22 ] proposed that rutin be added to poly( l -lactide- co -glycolide) (PLGA) solution and then electrospun to obtain antibacterial nanofibrous mats. However, reports related to the UV resistance of rutin-contained nanofibrous mats are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…PLGA, a polyester of hydroxy acids, is one the most biocompatible, biodegradable and injectable polymers approved by the FDA for many biomedical and therapeutic applications, ranging from DDSs to tissue engineering. [154][155][156] Although PLGA is a glassy synthetic polymer, it has a quite rigid structure along with remarkable mechanical strength, permitting its use as CDDSs. Besides, PLGA copolymers possess high ratios of lactic acid which are less hydrophilic than functional groups in PGA, absorbing less water and consequently are more slowly degradable.…”
Section: Applications Of Plga Blends In Cddssmentioning
confidence: 99%
“…PLGA-based drug delivery systems can be easily formed into any shape and size, such as particles, fibres, scaffolds, films, and coatings, and they can be used to incorporate and deliver a wide range of synthetic and natural drugs [ 10 , 11 ]. Numerous hydrophobic agents have been incorporated into PLGA matrices with proven antimicrobial efficiency, for example, chlorhexidine [ 12 ], essential oils from clove [ 13 ] or thyme [ 14 ], the flavonoids quercetin [ 15 ] and rutin [ 16 ], the monoterpenes carvone [ 17 ] and carvacrol [ 18 ], the phenylpropanoids anethole [ 17 ], cinnamaldehyde [ 19 ], and eugenol [ 19 ], a plant extract from guabiroba [ 20 ], and the steroid-like antibiotic fusidic acid [ 21 ].…”
Section: Introductionmentioning
confidence: 99%